A Clinical Study of Switrahara Churna in Switra (Vitiligo) as Lepa (AYUSHDHARA, 2022)
Switra can be compared with Vitiligo of contemporary science. Switra is a pigmentary disorder of great socio-medical importance and defined as, acquired, idiopathic, hypo melanosis of skin and hair. Aims and objectives: Therapeutic evaluation of Switrahara Churna on Switra. Materials and Methods: In present study, total 32 patients with signs and symptoms of Switra were selected from the OPD, Rasa Shastra and Bhaishjya Kalpana of S.V Ayurvedic hospital T.T.D Tirupati. Out of them 30 patients completed the course of treatment. Follow up was done every 15th day. The assessment criteria were Twak Swetata, Twak Rukshta, Kandu Daha Twak, Vivarnata and margins. Statistical analysis was carried out using “Analysis tool pack add-in of Microsoft Excel- 2019” and “Graph pad Prism Version- 7” by applying paired ‘t’- Test. Results: Among 30 patients, 18 patients (60%) had moderate improvement, 11 patients (36%) had marked improvement, 1 patient (3.33%) had mild improvement. Conclusion: The therapy in the form of Lepa i.e., Switrahara Churna is a safe and effective in the management of Switra.